A study on brick using fine coconut shell - Siti Zul Norain, Muhamad (2019)
The rising cost of building materials in the construction industry nowadays, has a major impact on the society. Therefore, the use of new materials in the replacement of sand to produce more environmental-friendly bricks using by products were carried out. Coconut shell is one of the waste materials produced from the agricultural process. This matter indirectly poses a challenge to the parties involved in dealing with the disposal as well as the environmental management. This study was conducted to investigate the bricks properties effect of using fine coconut shell which comprised of 0%, 2.5% and 7.5% as replacement for sand. The 0% replacement of fine coconut shell are used to compare the data with a sample that contains fine coconut shell. 40 bricks that composed of fine coconut shell and 20 bricks with nil content of the fine coconut shell were tested in this study. The size of the bricks is 225 mm x 115 mm x 75 mm with a standard mixture of cement: sand, with the ratio of 1:6 were used in this study. The mixture of bricks were treated with water curing methods for 7th and 28th days. The properties of the samples were determined by two tests, which are compressive strength test and water absorption test and were implemented at 7th and 28th days. Based on the results of the test, the strength of the samples were decreased when the percentage usage of fine coconut shell was increased. Then, the water absorption rate was increasing as the percentage usage of fine coconut shell increases. Thus, the overall result of this tests shows that the optimum value of brick using fine coconut shell as a sand replacement is 2.5%, which is it performs the best properties compared with 7.5%. This study proves that the use of coconut shell as replacement for sand in sand brick helps in reducing the construction costs as well as can reduce the wastes at the landfill sites.